Perceptions of sexual coercion: learning from young people in Ibadan, Nigeria (2001)
This study explored the problem of sexual coercion from the perspectives of 77 young people aged 14-21 in Ibadan, Nigeria, the behaviours they perceive to be sexually coercive and the contexts in which these occur through four narrative workshops. Participants were drawn from two secondary schools and 15 apprentice workshops. All four groups identified similar coercive behaviours and developed narratives of the events that typically lead up to them. Behaviours included rape, unwanted touching, incest, assault, verbal abuse, threats, unwanted kissing; forced exposure to pornographic films, use of drugs for sedation and traditional charms for seduction, and insistence on abortion if unwanted pregnancy occurs. Men were typically the perpetrators and young women the victims. Perpetrators included acquaintances, boyfriends, neighbour, parents and relatives. All the narratives revealed the inability of young people to communicate effectively with each other and resolve differences. The results suggest the need for life-skills training that facilitates communication, seeks to redress gender power imbalances, teaches alternatives to coercion as a means of resolving conflict over sexual relations and respect for sexual and reproductive rights, and provides victims with information on appropriate services, support and referral.